2017
DOI: 10.14507/epaa.25.2205
|View full text |Cite
|
Sign up to set email alerts
|

Equitable leadership on the ground: Converging on high-leverage practices

Abstract: What would leadership standards look like if developed through a lens and language of equity? We engaged with a group of 40 researchers, practitioners, and community leaders recognized as having expertise on equity in education to address this question. Using a Delphi technique, an approach designed to elicit expert feedback and measure convergence around a question of interest, these leaders participated in three rounds of data gathering. In Rounds One and Two, the 40 participants described and then rated lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 54 publications
0
17
0
Order By: Relevance
“…Without additional theory development to aid school leaders, this chasm will become larger as SEL is brought to scale, measured, and perhaps included in accountability systems (West, Buckley, Bartolino Krachman, & Bookman, 2017). And while numerous frameworks for leadership may lend themselves to successful affective reform implementation-consider equity-oriented leadership (Galloway & Ishimaru, 2017), caring leadership (Bass & Alston, 2018;Del Carmen Salazar, 2013;van der Vyver, van der Westhuizen, & Meyer, 2014), ethical school leadership for undocumented immigrant students (Crawford, 2017), engaged school leadership (Beard, 2018), and social justice leadership (Rigby, 2014;Theoharis, 2007)-these frameworks focus on the general, the whole school, or academic reforms. Current frameworks do not go so far as to explicitly examine the implementation of affective or SEL initiatives.…”
Section: Toward a Framework For Leadership Of Sel Reformsmentioning
confidence: 99%
See 1 more Smart Citation
“…Without additional theory development to aid school leaders, this chasm will become larger as SEL is brought to scale, measured, and perhaps included in accountability systems (West, Buckley, Bartolino Krachman, & Bookman, 2017). And while numerous frameworks for leadership may lend themselves to successful affective reform implementation-consider equity-oriented leadership (Galloway & Ishimaru, 2017), caring leadership (Bass & Alston, 2018;Del Carmen Salazar, 2013;van der Vyver, van der Westhuizen, & Meyer, 2014), ethical school leadership for undocumented immigrant students (Crawford, 2017), engaged school leadership (Beard, 2018), and social justice leadership (Rigby, 2014;Theoharis, 2007)-these frameworks focus on the general, the whole school, or academic reforms. Current frameworks do not go so far as to explicitly examine the implementation of affective or SEL initiatives.…”
Section: Toward a Framework For Leadership Of Sel Reformsmentioning
confidence: 99%
“…Additionally, leaders should hire caring teachers who have the potential to be inclusive and believe in the power of their students to succeed on both SEL and academic measures. Galloway and Ishimaru (2017) further suggested that leaders ought to consider building leadership pipelines of equity-minded, marginalized teachers (p. 385).…”
Section: Toward a Framework For Leadership Of Sel Reformsmentioning
confidence: 99%
“…I must take note here that the practice perspective in teaching is contested territory. The Core Practices Research community (McDonald et al, 2013) and the High Leverage Practice community (Galloway & Ishimaru, 2017) take a different view of practice and yet we use the same term. I am certain that this work is rigorous, conceptually rich and well-intentioned in its effort to shift from a fossilized consideration of teacher knowledge to a focus on what teachers are doing and how they are engaged.…”
Section: Consider Practicementioning
confidence: 99%
“…Lahey, Pepe and Nelson (2017) indicated that ethical principles are foundational to organizational values. Similarly, values such as democracy, equity and accountability are mainly emphasized in relation to ethical leadership (Galloway & Ishimaru, 2017). Aronson (2001) mentioned about two main ethical theories, namely, deontology and teleology, and considered directive, transactional and transformational leadership styles related to ethical leadership and its values.…”
Section: Introductionmentioning
confidence: 99%